2023
DOI: 10.1039/d2an02020c
|View full text |Cite
|
Sign up to set email alerts
|

Sum frequency generation spectroscopy of fluorinated organic material-based interfaces: a tutorial review

Siwakorn Sakunkaewkasem,
Daniela Deleon,
Yunsoo Choi
et al.

Abstract: Molecular interactions at interfaces have a significant effect on the wetting properties of surfaces on a macroscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In particular, the detection depth of SFG spectroscopy is usually at the nanoscale, while the definition of interfacial depth in macro-experiments such as zeta potential is ambiguous; (2) more advanced experimental techniques on the atomic scale are yet to be developed. Most experiments aimed at identifying the acid–base nature of interfaces rely on indirect measurements. ,,, Although the OH dynamics of water molecules at the first interfacial hydration layer can be observed by vibrational SFG spectroscopy, which helped to probe the interfacial protons of a 1 M HCl solution, the in-operando detection of ionic distribution along the interfacial depth of the neutral water system with the standard surface-science methods is still challenging. By combining with simulation technologies, deeper atomic-scale perspectives can be achieved. In terms of theoretical computations, the modeling scale of accurate AIMD, which is usually limited to simulations for hundreds of water molecules and hundreds of picoseconds due to the expensive computational cost, is far from the actual interface scale and dynamic time scale, so it is possible that these simulation results were slightly deviated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the detection depth of SFG spectroscopy is usually at the nanoscale, while the definition of interfacial depth in macro-experiments such as zeta potential is ambiguous; (2) more advanced experimental techniques on the atomic scale are yet to be developed. Most experiments aimed at identifying the acid–base nature of interfaces rely on indirect measurements. ,,, Although the OH dynamics of water molecules at the first interfacial hydration layer can be observed by vibrational SFG spectroscopy, which helped to probe the interfacial protons of a 1 M HCl solution, the in-operando detection of ionic distribution along the interfacial depth of the neutral water system with the standard surface-science methods is still challenging. By combining with simulation technologies, deeper atomic-scale perspectives can be achieved. In terms of theoretical computations, the modeling scale of accurate AIMD, which is usually limited to simulations for hundreds of water molecules and hundreds of picoseconds due to the expensive computational cost, is far from the actual interface scale and dynamic time scale, so it is possible that these simulation results were slightly deviated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various probing methods, sum frequency generation vibration spectroscopy (SFG-VS) is a second-order nonlinear technique with unique interface sensitivity and selectivity; it can reveal the molecular-level structures and their changes at the interfaces. For example, Maia and Miranda studied the chain structures of conjugated polymers at the buried interface between polymers and metals and observed different thiophene ring orientations on different metallic substrates or from different film-forming processes . Li et al investigated the buried interface between nylon and modified polyethylene and reported that the interfacial adhesion between nylon and modified polyethylene was enhanced by the formation of a covalent bond via the consumption of N–H groups at the buried interface .…”
Section: Introductionmentioning
confidence: 99%